Nondestructive 2-D geoelectrical surveying into a building's basement - Athanasiou, E.; Tsourlos, P.; Vargemezis, G.; Tsokas, G. (Bulletin of the Geological Society of Greece, 2007)
In this paper the application of flat base electrodes into a building's basement is examined. The aim of this study was to locate ancient walls possibly situated underneath a building, lying on Ag. Dimitriou road in Thessaloniki (Greece). During ERT surveying, an archaeological excavation took place on the roadway outside the building. The excavation revealed ancient walls. A number of resistivity profiles were carried out on the concrete floor of the building. The dipole-dipole array was used in some sections, while in others the Wenner array was undertaken. The spacing "a" between electrodes was Im and the maximum N-separation of Nmax=8. In order to perform resistivity profiles in a nondestructive manner on the concrete floor, flat base electrodes were applied. The resistivity surveying indicated the existence of linear structures identified as resistive bodies. These anomalies may have been derived from various causes, but most likely they may have been derived from the continuation of the ancient walls revealed from the archaeological excavation on the roadway. Finally, it must be noted that flat base electrodes proved to be an efficient tool for measuring indoors.